Estudio de factibilidad para la implementación de un sistema de información para el control de merma en la producción bananera en la empresa SUMIFRU. - Vera Macias, Jonathan Kenny (2022)
The present titling work consists of carrying out a feasibility study for the implementation of an information system for the control of waste in banana production in the Sumifru company. Being this multinational company based in the country for approximately eight years. Dedicated to the production of bananas in the province of Los Ríos and Guayas. With its headquarters in the city of Guayaquil; in the Baba canton it has the production matrix in which it does not have the technological tools to determine the volume of waste on the days of cutting, for which it is to check surveys of the company's collaborators in which the need was evidenced to create an information system that is efficient, effective and timely for decision-making in the quality and production departments. The applied research method is Inductive-Deductive, which allowed the analysis of economic and operational feasibility.